Fibre-assisted expansive mortar for high-efficiency rock fracturing - Lee, Elton Zi Zong (2019)
It is a well-established fact that the conventional rock and concrete fracturing methods, such as blasting and hydraulic fracturing, inevitably produce environmental pollution as a by-product. In efforts to reduce the detrimental impact on the environment, a new alternative to the conventional fracturing methods known as the Soundless Chemical Demolition Agent (SCDA) has been experimented with. However, very little research has been done on SCDA, and its effectiveness outside of the limited details given by manufacturers are unknown. Previous studies on concrete and mortars have shown that there is an improvement on the overall durability and tensile strength of the material when fibres are added to these materials. Hence, in this project, the effectiveness of adding fibre to SCDA, a type of expansive mortar, were explored. Steel fibre was used in this study. The design of experiment for this project serves to determine if fibre-assisted expansive mortar is more effective in fracturing rocks as compared to expansive mortar alone. Samples of granite cylinders were prepared with boreholes drilled in them. In order to induce brittle failure in granite, half of the granite cylinders have SCDA added to the boreholes, while the other half have SCDA and steel fibre added to the boreholes. The strain gauges were attached to each individual granite cylinder and the exact time taken to reach brittle failure for each cylinder was recorded. This was done to determine the effectiveness of the addition of steel fibre on SCDA. To determine if the fibre-assisted SCDA is more effective under constrained environment, a further experiment was done on the granite cylinders with fibre-assisted SCDA. By using a steep clamp, the two ends of the borehole were blocked, giving it both top and bottom constrains. Through the results, it can be determined if the radial expansion of the SCDA was improved through the addition of steel fibres. If so, fibre-assisted expansive mortar could be a key to high-efficiency rock fracturing.